Identification of a norovirus outbreak on a hematopoietic stem cell transplant unit and development and implementation of a novel infection prevention algorithm for controlling transmission - Branch-Elliman, Westyn (2020)
Controlling norovirus transmission in units with immunocompromised patients is challenging. We present a cluster of norovirus cases that occurred on a stem-cell transplant unit and the prevention efforts that were implemented to limit the outbreak. Protocols developed to control this cluster may provide a model for other facilities.